Luke-Acts: Political Biography/Historyunder Rome : on Gender and Ethnicity - Balch, David L. (Zeitschrift für die neutestamentliche Wissenschaft, 2020)
In the Hellenistic-Roman world, both philosophical schools (Platonists) and ethnic groups (Romans, Athenians, Judeans) were committed to the authority of founder figures. Dionysius, Josephus, and Luke included biographies of their founders (Romulus, Moses, Jesus) within their historical works. Luke-Acts also acculturated Roman politics: 1) Luke narrated the official leadership of early Pauline assemblies exclusively by males, not narrating earlier leadership by women (Junia, Euodia, Syntyche). 2) Luke gave Jesus an inaugural address “to declare God’s age open and welcome to all [nations]” (Luke 4:19 quoting Isa 61:2), urging Luke’s auditors to become multiethnic. Peter instituted this crossing of ethnic boundaries in Judea (Acts 10) and Paul “accepted all” in Rome (Acts 28:30), the concluding sentence of the two volumes.